In Keats's Haggard Shadow : Reading Dr Haggard’s Disease as a Postmodernist Comment on Keats and Keatsian Romanticism - Vermeulen, Jeroen (International Journal of English Studies, 2021)
This article discusses how John Keats’s biography and poetry exerted influence on the development of the plot, structure, protagonists and metaphorical framework of Patrick McGrath’s novel Dr Haggard’s Disease (1993). Furthermore, it contends that the novel does not simply aim to pay tribute to Keats or to function as a literary emulation or even mimicry of Keats’s life and oeuvre. Instead, the novel suggests a postmodernist comment on Keatsian Romanticism as expressed in Keats’s poetry. An interpretation of Dr Haggard’s Disease as historiographic metafiction with an emphasis on the intertextual links between McGrath’s novel and Keats’s work makes clear that the novel’s narrator and protagonist, Edward Haggard, by way of subversion and distortion devaluates the Keatsian dichotomies of real/ideal and Truth/Beauty.